A la carte globalism: On firm internationalization in Portugal. - Coelho, J. V. (Plataforma Barómetro Social, 2021)
The rising number of Portuguese companies with international operations and growing sectoral diversification has been contributing to the recent international expansion of the Portuguese economy. It is important to introduce nuances in these recent developments, as the proportion of international firms and internationalization density index are still low. This article presents the results of a research project carried out between 2015 and 2018 focused on studying firm internationalization logics observable in Portugal, in three emergent contributing sectors – Retail, Construction and Software Development. Results present domestic markets has having a diffluent role and indicate that internationalization processes are valued for their portability and reversibility - a landscape named as à la carte firm internationalization. Room exists for de- and re-internationalization, an expression of managerial attempts to leverage resource constraints and hyphenated access to global markets, clients and value chains.